Factors influencing growth of fashion leather shoes. A review of literature - Kelion, Dr. Elizabeth (International Journal of Fashion and Design, 2021)
Purpose: The purpose of this research was to investigate the factors influencing growth of fashion leather shoes. A review of literature. Methodology: The study adopted a desktop literature review method (desk study). This involved an in-depth review of studies related to factors influencing growth of fashion leather shoes. This article reviewed recorded sources to present the current state of leather shoe industry. Results: Availability of raw materials considered factors such as the cost of production, the quality of raw materials locally available as well as having already established centers from which these raw materials are sourced from. Some of the legally related factors captured in this study included government incentives, government initiated programs, export taxes, trade policies already in place and the licensing that takes place in the various levels involved in the production of leather footwear. Market related factors consisted of affordability of the leather footwear, quality design, skill training and branding. All these factors significantly contributed to the existence of this positive relationship. Unique contribution to theory, practice and policy: It's recommended that Leather Industries should employ strategies that maintain this relationship and also ensure that it's sustainable. The most important aspect to be considered in using the raw materials is determining the kind of quality used. The farmers should be educated on how well they should take care of the animals as well how best to dispose the hides used so as to ensure the end product which is the shoe is of good if not high quality. Additionally, it's recommended that the government reduces on the number of licensing for the leather footwear producers. The taxes and duties also paid discourages growth in this industry.